Vandalisme Menurut Perspektif Islam Dan Pasal 406 Ayat (1) KUHP - Santana Suryapringgana; Tajul Arifin (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
It can be understood that vandalism is an anarchist act which is also can be equated with graffiti, desecration and even destruction of public facilities. In general, this is done by young people who are looking for their identity and existence in their lives, but it cannot be denied that vandalism is carried out by many groups for different reasons. In this article, which uses descriptive qualitative research methods, we will examine Vandalism in more depth and relate it to Article 406 paragraph (1) of the Criminal Code and the Islamic perspective. In the purpose of being able to understand Vandalism which is studied and examined with related regulations and prohibitions as well as the perspective of Islamic law. This research found information that vandalism can be prosecuted and sanctioned in accordance with Article 406 paragraph (1) of the Criminal Code, as well as an Islamic perspective.